Adherence to colorectal cancer screening in a private health insurance center in Argentina from 2008 to 2022 - Sguiglia, Sebastián; Volij, Camila; Rodríguez-Tablado, Manuel; Terrasa, Sergio; Esteban, Santiago (Revista peruana de medicina experimental y salud pública, 2025)
Motivation for the study. There is a need for information on population adherence to colon cancer screening. Main findings. Adherence to screening in health insurance increased to a maximum of 47.1% in December 2022, which is below desirable targets. The most commonly used method was colonoscopy. Public health implications. This information could contribute to the design of a multicomponent intervention to improve adherence to colon cancer screening. In order to evaluate adherence to colorectal cancer (CRC) screening among members of the Health Plan of the Hospital Italiano de Buenos Aires in Argentina, we conducted a retrospective cohort study using secondary data from the electronic medical record. We included all members over 50 years of age during the period 2008-2022. We assessed the number and type of screening tests performed and the proportion of members covered for screening. We analyzed 112,112 participants, with a median age of 58.6 years and a follow-up time of 8.6 years. Colonoscopy was the most commonly used test. The maximum coverage reached was 47.1% in December 2022. In conclusion, adherence to CRC screening was suboptimal, as was the method used. This information can be used for the design of a multicomponent intervention.